PENGEMBANGAN SISTEM INFORMASI PERIJINAN TENAGA KESEHATAN DENGAN MENGGUNAKAN METODE BACK END DAN FRONT END - Arhandi, Putra Prima (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
Dinas Kesehatan Kabupaten Pasuruan is a part of SKPD unit of Pasuruan district, one of the main task of this unit is to ensure a good health care service to the community. In order to ensure good health care service Dinas Kesehatan Kabupaten Pasuruan provide a licensing service for health workforce, this licensing service divided into two main license which is license for work and licence for practice. This licensing service is used by healtchare workforce such as doctor, midwife, nurse, pharmacist, therapists and nutritionists. To facilitate this licensing service Dinas Kesehatan Kabupaten Pasuruan created an information system. This information system have to be realiable and able to accelerate the process to get a practice license or work license for healthcare workforce. This information system must be accessible via desktop, web or a mobile device. Therefore in this research the information system is developed using back end and front end method. By using this method we produce a siginificant speed in application response time with 114 milli second response time for login request and 47 milli second for get request.Kata kunci:Information system, back end, front end